A contraindication to metfromin therapy: Renal impairment - Adherence to prescribing guidelines at a hospital in Turkey - Taner, Neda; Çattık, Büşra Nur; Berk, Barkın (University of Istanbul, 2018)
Objective: The aim of this study was to investigate whether renal functions of the patients were monitored and checked before and during metformin treatment as recommended in guidelines or whether they were disregarded and metformin was prescribed despite the contraindication of renal impairment in a hospital in Turkey. Method: This retrospective cross-sectional study was conducted among the patients who were hospitalized at a university hospital, diagnosed with type 2 diabetes mellitus and had metformin included in their treatment between 2015-2016. The total number of patients with this diagnosis and treatment between these years was determined as 66 and all the patients were taken into the study. Renal functions of these patients were assessed by measuring serum creatinine levels and calculating GFR using the Cockcroft- Gault formula. Results: During the duration of metformin treatment 10 patients (15%) were not monitored for their serum creatinine. The 56 patients who were monitored for their serum creatinine were at 1, 2, 3, 4, 5 (end-stage) renal failure stages with the rates of 30, 36, 30, 4, 0% respectively. Conclusion: Assessment of renal function, adjustment of drug doses accordingly and termination of the treatment when contraindicated, are essential strategies for metformin therapy to prevent medication errors. However, this study showed that adherence to these prescribing rules are low and in some patients renal function was not monitored, placing them in increased risk of lactic acidosis.
Keywords: Lactic Acidosis; Metformin; Renal Function